Review on Recent Advances in Pulse Detonation Engines - K. M. Pandey; Pinku Debnath (Journal of Combustion)
Pulse detonation engines (PDEs) are new exciting propulsion technologies for future propulsion applications. The operating cycles of PDE consist of fuel-air mixture, combustion, blowdown, and purging. The combustion process in pulse detonation engine is the most important phenomenon as it produces reliable and repeatable detonation waves. The detonation wave initiation in detonation tube in practical system is a combination of multistage combustion phenomena. Detonation combustion causes rapid burning of fuel-air mixture, which is a thousand times faster than deflagration mode of combustion process. PDE utilizes repetitive detonation wave to produce propulsion thrust. In the present paper, detailed review of various experimental studies and computational analysis addressing the detonation mode of combustion in pulse detonation engines are discussed. The effect of different parameters on the improvement of propulsion performance of pulse detonation engine has been presented in detail in this research paper. It is observed that the design of detonation wave flow path in detonation tube, ejectors at exit section of detonation tube, and operating parameters such as Mach numbers are mainly responsible for improving the propulsion performance of PDE. In the present review work, further scope of research in this area has also been suggested.